Antibacterial and wound-healing action of Ulmo honey (Eucryphia cordifolia) of differing degrees of purity - Muñoz, Mariela; del Sol, Mariano; Vásquez, Bélgica (Frontiers in Veterinary Science, 2023)
Introduction Antibacterial properties of honey vary according to its floral origin; few studies report the percentage of pollen types in honey, making it difficult to reproduce and compare the results. This study compares the antibacterial and wound-healing properties of three kinds of monofloral Ulmo honey with different percentages of pollen from Eucryphia cordifolia. Methods The pollen percentage of the honey was determined by melissopalynological analysis, and they were classified into three groups: M1 (52.77% of pollen from Eucryphia cordifolia), M2 (68.41%), and M3 (82.80%). They were subjected to chemical analysis and agar diffusion test against Staphylococcus aureus. A total of 20 healthy adult guinea pigs (Cavia porcellus) of both sexes were randomly assigned to four groups for experimental burn skin wound (uninfected) production and treatment with Ulmo honey. On day 10 post-injury, biopsies were obtained, and histological analysis was performed to assess wound-healing capacity following the treatment with honey. Results The chemical analysis showed that M3 differed significantly from M1 in terms of pH (P = 0.020), moisture (P = 0.020), total sugars (P = 0.034), and total solids (P = 0.020). Both strains of Staphylococcus aureus were susceptible to M1 and M2 at 40% w/v but were resistant to M3 at all concentrations. All groups (I–IV) were in the initial proliferative phase, with complete or partial re-epithelialization of the epidermis. Discussion The antibacterial activity showed a wide range of variation in the different types of honey studied, with no significant differences between wound healing and pollen percentage in the groups studied. Higher pH and the absence of Tineo in M3 conferred a lower antibacterial capacity but not a lower wound healing capacity. Despite its variability in the percentage of Eucryphia cordifolia like primary pollen in Ulmo's monofloral honey, this has the same properties in relation to wound healing.